Gambaran Status Gizi Balita Usia 1-5 Tahun dengan Riwayat Berat Badan Lahir Rendah di Posyandu Catleya 95B Kabupaten Jember - Putri Proyono, Dicka Indo; Wahyuni, Ida; Rofiyah, Rofiyah (Jurnal Vokasi Kesehatan, 2025)
Nutritional status in toddlers is a critical indicator of health and development, particularly among those with a history of Low Birth Weight (LBW), who are at higher risk of experiencing growth and nutritional issues. This study aims to describe the nutritional status of children aged 1–5 years with a history of LBW at Posyandu Catleya 95B, Jember Regency. A quantitative descriptive design with a cross-sectional approach was used. The sample consisted of 21 toddlers selected through total sampling. Data were collected using anthropometric measurements and analyzed based on WHO standards. The results showed that most children were aged 3–5 years (57.2%) and were female (52.3%). Regarding nutritional status, the majority had normal nutritional status (81%), while 14.2% were undernourished and 4.8% were overweight. No cases of severe malnutrition were found. These findings suggest that while most toddlers with a history of LBW have achieved normal nutritional status, ongoing monitoring and nutritional interventions remain essential to prevent future nutritional problems.